Influence of blood storage age on immune and coagulation parameters in critically ill transfused patients - Norris, Philip J.; Schechtman, Ken; Inglis, Heather C.; Adelman, Avril; Heitman, John W.; Vilardi, Ryan; Shah, Avani; Roubinian, Nareg H.; Danesh, Ali; Guiltinan, Anne M.; Keating, Sheila M.; Lacroix, Jacques; et al. (Transfusion (Philadelphia, Pa.), 2019)
BACKGROUND Several retrospective studies have suggested that transfusion with red blood cells (RBCs) stored for longer periods is associated with increased mortality. The Age of Blood Evaluation (ABLE) study randomized subjects to receive fresh vs. standard issue RBC units and showed no difference in the primary or secondary endpoints of mortality or change in multi‐organ dysfunction syndrome (MODS) score. METHODS In this study a subset of 100 ABLE subjects were enrolled to measure coagulation and immune parameters. Samples were collected pre‐transfusion and on days 2, 6, 28, and 180 post‐transfusion. Levels of 16 coagulation parameters, regulatory and functional T cells, 25 cytokines, and 16 markers of extracellular vesicles (EVs) were determined. RESULTS Changes from baseline in levels of protein C, factor V, and EVs expressing phosphatidyl serine and CTLA‐4 (CD152) differed between recipients of fresh and standard storage age RBC units, with the vast majority of coagulation and EV markers and all cytokines tested showing no difference between study arms. Although most analytes showed no difference between subjects in the fresh and standard arms of the study, 6 coagulation parameters, 15 cytokines, and 7 EV parameters changed significantly in the period post‐transfusion. DISCUSSION Transfusion of fresh vs. standard issue RBC units does not result in substantial changes in coagulation or immune parameters, up to day 35 of RBC storage. Furthermore, significant changes in multiple coagulation and immune parameters are detectable post‐transfusion, though causality cannot be determined based on the current study.